2021
DOI: 10.1021/acs.inorgchem.1c01151
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Cobalt-Incorporated MOF-5 Microfibers as a Promising Electrocatalyst for OER in Alkaline Media

Abstract: Metal−organic framework (MOF)-based materials have attracted attention in recent times owing to their remarkable properties such as regulatable pore size, high specific surface area, and elasticity in their network topology, geometry, dimension, and chemical functionality. It is believed that the incorporation of a MOF network into a fibrous matrix results in the improvement of the electrocatalytic properties of the material. Herein, we have synthesized a Co-incorporated MOF-5-based fibrous material by a simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…Figure b,c present the high-resolution XPS spectra for Co 2p and Fe 2p. The Co 2p spectrum of Co 0.1 Fe 0.4 -HQ/CF before OER shows two bands at 781.6 and 796.9 eV with two shake-up satellites at 786.0 and 802.6 eV, suggesting the presence of Co 2+ in the product . It is noted that the shift of the cobalt XPS bands with the oxidation state is quite different from those of other elements due to the so-called final state effect.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Figure b,c present the high-resolution XPS spectra for Co 2p and Fe 2p. The Co 2p spectrum of Co 0.1 Fe 0.4 -HQ/CF before OER shows two bands at 781.6 and 796.9 eV with two shake-up satellites at 786.0 and 802.6 eV, suggesting the presence of Co 2+ in the product . It is noted that the shift of the cobalt XPS bands with the oxidation state is quite different from those of other elements due to the so-called final state effect.…”
Section: Resultsmentioning
confidence: 72%
“…The Co 2p spectrum of Co 0.1 Fe 0.4 -HQ/ CF before OER shows two bands at 781.6 and 796.9 eV with two shake-up satellites at 786.0 and 802.6 eV, suggesting the presence of Co 2+ in the product. 50 It is noted that the shift of the cobalt XPS bands with the oxidation state is quite different from those of other elements due to the so-called final state effect. A red-shift of the XPS band occurs when the oxidation state is increased from Co(II) to Co(III).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…53 Also, the 1D porous structure also enables accelerated electron mobility during electrochemical reactions, rendering electrospun 1D nanofibers promising electrocatalysts for energy conversion. 54 Finally, it is also reported that the electrospun nanomaterials can also work as a support for the uniform dispersion of active components. 55 Benefitting from these advantageous merits, these electrospun nanomaterials can thus work as promising electrocatalysts to largely promote the catalytic activity and efficiency.…”
Section: Advantages Of Electrospun 1d Nanocatalystsmentioning
confidence: 99%
“…This triggered the researchers to design less expensive, more potent, and robust catalysts by surface engineering with more active sites to improve their activity. Recently, extensive efforts have been made for developing third-row transition-metal-based catalysts such as oxides, , oxyhydroxide hydrates, hydroxides, , phosphides, sulfides, chalcogenides, , carbon composites, , and layered double hydroxides (LDH) for efficient OER in alkaline medium by many research groups , Especially, transition metals like Ni-, Fe-, and Co-based materials are used for effective OER application in alkaline medium. Among them, Ni is an earth-abundant first-row transition metal and its related nanocatalysts have a high impact toward the alkaline OER because of their good water oxidation activity, with lower overpotential and Tafel slope value.…”
Section: Introductionmentioning
confidence: 99%